2015
DOI: 10.1007/s00404-015-3616-2
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal epithelium and microflora characteristics in women with premature ovarian failure under hormone therapy compared to healthy women

Abstract: Oral hormone therapy for young women with POF seems to be good enough to reestablish the epithelium cells, vaginal pH and microflora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…We found the vaginal microbiota to be increasingly diverse with increased species richness in the case of POF, and a significant shift in overall microbial diversity was observed. However, a previous cross-sectional study of microbiota failed to identify obvious differences between individuals in terms of vaginal microbiota diversity [28,29]. The strength of our study lies in the comprehensive description of microbial communities associated with POF achieved through the use of 16S rRNA sequencing; particularly, the association with clinical characteristics of POF; and the utilisation of predictive models to identify bacterial taxa that are differentially expressed in POF.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We found the vaginal microbiota to be increasingly diverse with increased species richness in the case of POF, and a significant shift in overall microbial diversity was observed. However, a previous cross-sectional study of microbiota failed to identify obvious differences between individuals in terms of vaginal microbiota diversity [28,29]. The strength of our study lies in the comprehensive description of microbial communities associated with POF achieved through the use of 16S rRNA sequencing; particularly, the association with clinical characteristics of POF; and the utilisation of predictive models to identify bacterial taxa that are differentially expressed in POF.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies on the vaginal microbiota in the case of POF have mainly involved amine test (or the Whiff test) [28], whereas our study focused on differences at the level of the genus. One of the most attractive features of 16S rRNA gene sequence informatics is the potential for genus identification [30].…”
Section: Discussionmentioning
confidence: 99%
“…We found the vaginal microbiota to be increasingly diverse with increased species richness in the case of POF, and a significant shift in overall microbial diversity was observed. However, a previous cross-sectional study of microbiota failed to identify obvious differences between individuals in terms of vaginal microbiota diversity [34,35]. The strength of our study lies in the comprehensive description of microbial communities associated with POF achieved through the use of 16S rRNA sequencing; particularly, the association with clinical characteristics of POF; and the utilisation of predictive models to identify bacterial taxa that are differentially expressed in POF.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies on the vaginal microbiota in the case of POF have mainly involved amine test (or the Whiff test) [34], whereas our study focused on differences at the level of the genus. One of the most attractive features of 16S rRNA gene sequence informatics is the potential for genus identification [36].…”
Section: Discussionmentioning
confidence: 99%
“…Bentti-Punto et al (2015) studied the effect of estrogen replacement therapy on the microflora and trophic state of vaginal epithelium, sexual function of women with early menopause, comparing them with women with persistent menstrual function. It has been shown that despite the absence of significant differences in the composition of the microbial landscape, the frequency of fungal infection, vaginal pH, women receiving hormone replacement therapy due to premature termination of ovarian function have a lower quality of sex life than their peers, mainly due to pain and decreased moisture [17].…”
Section: Menopausal Symptomsmentioning
confidence: 99%